EVOLUSI PEMIKIRAN EKONOMI ISLAM DI INDONESIA: DARI TRADISI KE MODERNISASI - Hasanah, Ulfanianatul; Madinatul, Nurlaila; Setianingrum, Nurul; Anggitaningsih, Retna (SEKOLAH TINGGI ILMU SYARIAH ABU ZAIRI BONDOWOSO, 2025)
This study explores the evolution of Islamic economic thought in Indonesia, from traditional practices to modernized systems. The scope includes tracing significant transformations in Islamic economics and its adoption in the financial and social sectors. The purpose of the study is to analyze how traditional Islamic economic principles have adapted to contemporary economic demands. Using a qualitative descriptive approach, this research employs library research to gather insights from academic works and historical documents. The findings reveal three major phases in the development of Islamic economic thought in Indonesia: the traditional phase, the modern phase marked by the establishment of Islamic financial institutions, and the contemporary phase, where Islamic finance has become more integrated into the national economy. The study concludes that, despite modernization, Islamic economics in Indonesia remains grounded in core principles of social justice, economic freedom, and responsibility. This evolution underscores the potential of Islamic economics to offer sustainable economic solutions aligned with both religious values and modern needs.